2015
DOI: 10.1091/mbc.e14-05-1026
|View full text |Cite
|
Sign up to set email alerts
|

Studying early stages of fibronectin fibrillogenesis in living cells by atomic force microscopy

Abstract: Fibronectin (FN) is an extracellular matrix protein that can be assembled by cells into large fibrillar networks, but the dynamics of FN remodeling and the transition through intermediate fibrillar stages are incompletely understood. Here we used a combination of fluorescence microscopy and time-lapse atomic force microscopy (AFM) to visualize initial stages of FN fibrillogenesis in living fibroblasts at high resolution. Initial FN nanofibrils form within <5 min of cell-matrix contact and subsequently extend a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…The authors respectively recorded correlative topography/fluorescence images of fixed cells which were incubated on fluorescently-labelled fibronectin for 4 and 16 h (Figure 7), and thereby acquired the structure information of fibronectin. Based on the fibronectin structure, they monitored the early fibrillogenesis dynamics at high resolution by time-lapse AFM, and they also found that Mn 2+ enhanced the early fibrillogenesis [57]. Oreopoulos et al reported the coupling of AFM and polarized TIRFM technique, which can correlate the topographic features and the information (e.g., molecular orientation, conformation and rotational mobility) provided by polarized TIRFM [58,59].…”
Section: Correlative Optical Microscopy/atomic Force Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors respectively recorded correlative topography/fluorescence images of fixed cells which were incubated on fluorescently-labelled fibronectin for 4 and 16 h (Figure 7), and thereby acquired the structure information of fibronectin. Based on the fibronectin structure, they monitored the early fibrillogenesis dynamics at high resolution by time-lapse AFM, and they also found that Mn 2+ enhanced the early fibrillogenesis [57]. Oreopoulos et al reported the coupling of AFM and polarized TIRFM technique, which can correlate the topographic features and the information (e.g., molecular orientation, conformation and rotational mobility) provided by polarized TIRFM [58,59].…”
Section: Correlative Optical Microscopy/atomic Force Microscopymentioning
confidence: 99%
“…( E ) Three-dimensional topography intuitively showing the FN fibril structure. Reproduced from [57] with permission.…”
Section: Figurementioning
confidence: 99%
“…The prerequisite of AFM measurements is immobilizing cells onto a substrate. Adherent cells can naturally grow and spread on the substrate [28], while suspended cells can be immobilized onto the substrate via poly-L-lysine electrostatic adsorption [29] or microfabricated devices (e.g., porous polymer membrane [30], microwell [31] and micropillar [32]). For mechanical measurements, the piezoelectric ceramic tube drives the AFM tip (as shown in Fig.…”
Section: A Cellular Elastic Propertiesmentioning
confidence: 99%
“…However, studies using conventional light microscopy techniques are unsuitable to resolve the earliest steps of fibrillogenesis occurring at the nanoscale. Atomic force microscopy (AFM)-based imaging has been used to visualize molecular-scale structural changes of FN fibrils extended through cellular (Gudzenko and Franz, 2015) or external forces (Szymanski et al, 2017). Nevertheless, AFM live-cell imaging still suffers from limited scan speeds and therefore cannot adequately time-resolve the earliest steps of FN fibrillogenesis, which occur on the scale of seconds to minutes.…”
Section: Introductionmentioning
confidence: 99%